Round-up of arbitrations in the renewable energy sector: Lessons for Portugal - Vaz Pinto,Filipe (2019)
This article purports to provide an overview of the regulatory incentives enacted in Spain, the Czech Republic and Italy to foster the production of energy from renewable sources, the measures that were subsequently passed to withdraw some or all of those incentives and, finally, the arbitrations against these States that ensued. In their concluding remarks, the authors seek to draw similarities and points of departure in the relevant case law, and from there derive lessons for the regulation of the renewable energy sector in Portugal.